2018
DOI: 10.1038/s41388-018-0454-2
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-mesenchymal transition (EMT) beyond EGFR mutations per se is a common mechanism for acquired resistance to EGFR TKI

Abstract: Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) is a major advance in treating NSCLC with EGFR-activating mutations. However, acquired resistance, due partially to secondary mutations limits their use. Here we report that NSCLC cells with acquired resistance to gefitinib or osimertinib (AZD9291) exhibit EMT features, with a decrease in E-cadherin, and increases in vimentin and stemness, without possessing any EGFR secondary mutations. Knockdown of E-cadherin in parental cells increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
133
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(141 citation statements)
references
References 48 publications
8
133
0
Order By: Relevance
“…The Src/FAK network converges on AKT and MAPK to sustain oncogenic signaling and induce EMT. Many of the RTK that signal through Src/FAK have been implicated in EMT-associated resistance to EGFR targeting agents (Tang et al, 2016;Ichihara et al, 2017;Nukaga et al, 2017;Weng et al, 2018).…”
Section: The Role Of Emt In Acquired Resistance To Egfr Tkis Emt Co-omentioning
confidence: 99%
See 1 more Smart Citation
“…The Src/FAK network converges on AKT and MAPK to sustain oncogenic signaling and induce EMT. Many of the RTK that signal through Src/FAK have been implicated in EMT-associated resistance to EGFR targeting agents (Tang et al, 2016;Ichihara et al, 2017;Nukaga et al, 2017;Weng et al, 2018).…”
Section: The Role Of Emt In Acquired Resistance To Egfr Tkis Emt Co-omentioning
confidence: 99%
“…Therefore, the use of epigenetic agents may be beneficial to combat phenotypic plasticity as part of acquired drug resistance. Indeed, several histone deacetylate inhibitors (HDACi), including entinostat and trichostatin A, have been shown to restore expression of CDH1 and promote sensitivity to EGFR TKIs in pre-clinical models of EGFR-mutant NSCLC (Sharma et al, 2010;Suda et al, 2011;Weng et al, 2018).…”
Section: Emt In the Absence Of Bypass Activationmentioning
confidence: 99%
“…Growing evidence has shown that in addition to the T790M mutation and MET amplification, EMT plays an important role in acquired resistance to EGFR-TKIs. EMT is an important process during malignant cancer progression, accompanied by upregulation of N-cadherin and vimentin and downregulation of E-cadherin (30). Furthermore, wound healing and Transwell assays were performed, and the results showed that HCC827GR cells contained high migratory and invasive ability compared with HCC827 cells (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…HSP90 is required for the stability and function of numerous oncogenic proteins, and its specific inhibitors display multiple anticancer effects [30][31][32]. On the other hand, Hakai is considered an oncogenic protein that was reported to be overexpressed in various cancers such as colon and lung cancer [16,19,20], furthermore, Hakai knockdown inhibits cell migration [33].…”
Section: Downregulation Of Hakai May Partially Account For the Pharmamentioning
confidence: 99%